Analysis of the Effect of Price on Students Purchase Interest Using Linear Regression - Yulia Risma Yanti; Novitasani Putri; Purwadi Purwadi (Sean Institute, 2026)
This study aims to analyze the effect of price on students’ purchase intention using a simple linear regression method. This research adopts a quantitative approach with data collected through questionnaires distributed to 94 student respondents. The independent variable is price, while the dependent variable is purchase intention. The results show that price has a positive and significant effect on students’ purchase intention, with a regression coefficient value of 0.58. This indicates that an increase in perceived price value will be followed by an increase in purchase intention. In addition, the coefficient of determination (R²) of 0.36 indicates that price explains 36% of the variation in purchase intention, while the remaining 64% is influenced by other factors outside this study. The significance test also shows that the effect of price on purchase intention is statistically significant. Therefore, it can be concluded that price is an important factor influencing students’ purchase intention, although other factors also play a role in the purchasing decision process.